2010
DOI: 10.1007/s11191-010-9313-4
|View full text |Cite
|
Sign up to set email alerts
|

Learning-Related Changes in Adolescents’ Neural Networks During Hypothesis-Generating and Hypothesis-Understanding Training

Abstract: Fourteen science high school students participated in this study, which investigated neural-network plasticity associated with hypothesis-generating and hypothesisunderstanding in learning. The students were divided into two groups and participated in either hypothesis-generating or hypothesis-understanding type learning programs, which were composed of 12 topics taught over a 12-week period. To measure change in student competence and brain networks, a paper & pencil test and an fMRI scanning session were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…As our study results show, 25 MRI neuroimaging studies on education-related topics since 2000 were reviewed and divided into three domains: cognitive function, science education, and brain development. In these studies, the theme of language acquisition has received the most attention (i.e., Xiang et al, 2012 ; Goldman and Manis, 2013 ; Borst et al, 2016 ; Braga et al, 2017 ; Hong et al, 2017 ; Giraldo-Chica and Schneider, 2018 ; Horowitz-Kraus et al, 2018 ), followed by mathematical learning (i.e., Cantlon et al, 2011 ; Gullick et al, 2011 ; Lee and Kwon, 2012 ; Lee et al, 2015 ). In research method, fMRI is generally applied to all three domains, while sMRI is only applied to the two domains of cognitive function and brain development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As our study results show, 25 MRI neuroimaging studies on education-related topics since 2000 were reviewed and divided into three domains: cognitive function, science education, and brain development. In these studies, the theme of language acquisition has received the most attention (i.e., Xiang et al, 2012 ; Goldman and Manis, 2013 ; Borst et al, 2016 ; Braga et al, 2017 ; Hong et al, 2017 ; Giraldo-Chica and Schneider, 2018 ; Horowitz-Kraus et al, 2018 ), followed by mathematical learning (i.e., Cantlon et al, 2011 ; Gullick et al, 2011 ; Lee and Kwon, 2012 ; Lee et al, 2015 ). In research method, fMRI is generally applied to all three domains, while sMRI is only applied to the two domains of cognitive function and brain development.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, the findings suggested that the two hypothesis processes do not occur in the same neural network and should be trained separately. Lee and Kwon (2012) also examined whether constant scientific reasoning training could alter brain activation regions and networks. They designed two parallel 12-week training program; while one required the participants to actively generate a hypothesis (hypothesis-generating), the other asked the participants to passively understand a hypothesis (hypothesisunderstanding).…”
Section: Science Educationmentioning
confidence: 99%
“…Although no prior study has examined brain network connectivity associated with open-ended hypothesis generation, a few studies have assessed univariate brain activity during closed-ended hypothesis generation (convergent thinking; Kwon et al, 2009). For example, in a longitudinal study, Kwon et al (2009) found that following 2 months of training undergraduates how to generate accurate hypotheses (with a single/correct solution), brain activity increased within the left inferior frontal gyrus (IFG) of the ECN, as well as the anterior cingulate cortex of the SN (compared to a control group; Lee & Kwon, 2012). Other studies have examined cognitive processes relevant to scientific creative thinking, such as analogical transfer and abductive reasoning (H. Zhang et al, 2014).…”
Section: The Present Researchmentioning
confidence: 99%